Effects of plyometric training on explosive strength, acceleration capacity and kicking speed in young elite soccer players - Sedano, S.; Matheu, A.; Redondo, J. C.; Cuadrado, G. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The main aim of this study was to determine the effects of a 10-week plyometric training program on explosive strength, acceleration capacity and kicking speed in young elite soccer players. METHODS: Twenty-two players participated in the study: control group (CG), (N.=11; 18.2±0.9 years) and treatment group (TG) (N.=11; 18.4±1.1 years). Both groups performed technical and tactical training exercises and matches together. However, the CG players followed the regular physical conditioning program, which was replaced by a plyometric program for TG. Plyometric training took place three days a week and included jumps over hurdles, horizontal jumps and lateral jumps over hurdles. Jumping ability, 10 m sprint and kicking speed were measured on five separate occasions. RESULTS: Two-way analysis of variance (ANOVA) with repeated measures reflected that the TG demonstrated significant increases (P<0.05) in jumping ability and acceleration capacity after six weeks of training and in kicking speed with dominant and non-dominant leg after eight and ten weeks respectively. On the other hand there were no significant changes in CG players throughout the study. CONCLUSION: The main findings revealed that a 10-week plyometric program may be an effective training stimulus to improve explosive strength compared to a more conventional physical training program. The improvements in explosive strength can be transferred to acceleration capacity and kicking speed but players need time to transfer these increases.